SP10.2.6 The Quantitative Impact of COVID-19 on surgical training in the United Kingdom. (28th October 2021) - Clements, Joshua; Burke, Joshua; Hope, Carly; Nally, Deirdre; Griffiths, Gareth; Lund, Jon
Abstract: Aims: COVID-19 has had a global impact on all aspects of healthcare including surgical teaching and training. This study aimed to quantify the impact of COVID-19 on operative case numbers recorded by surgeons in training, and annual review of competency progression (ARCP) outcomes in the United Kingdom. Methods: Anonymised operative logbook numbers were collated from e-logbook and ARCP outcome data were collated from the Intercollegiate Surgical Curriculum Programme (ISCP) database for trainees across core and the ten higher surgical specialities. Operative logbook numbers and ARCP outcomes were compared between pre-COVID dates. Effect sizes are reported as incident rate ratios (IRR) with 95% confidence intervals (CI). Results: 5599 surgical trainees in 2019 and 5310 in 2020 in surgical specialty training were included. The IRR was reduced across all subspecialties because of the COVID-19 pandemic (0.55; 95% CI 0.53-0.57). Elective surgery (0.60; 95% CI 0.59-0.61) was affected more than emergency surgery (0.88; 95% CI 0.86-0.89). Regional variance with reduced operative activity was demonstrated across all specialities. 1 in 8 in their final year of training have not been able to achieve curriculum requirements and have had training extended. 1 in 4 trainees entering their final year of training are behind their expected training trajectory. Conclusion: COVID-19 continues to have a significant impact on surgical training in the UK. Urgent, co-ordinated action is required by key stakeholders to mitigate for these effects and maintain future surgical training.